Implementasi Fuzzy Logic Dalam Menentukan Persepsi Masyarakat Pendatang - Silky Safira; Wifra Safitri (Ikatan Ahli Informatika Indonesia, 2019)
The abstract is to be in fully-justified italicized text, at the top of the paper with single column as it is here, below the author information. Use the word “Abstract” as the title, in 10-point Times, boldface type, left relative to the column, initially capitalized. The abstract is to be in 10-point, single-spaced type, and up to 200 words in length. Leave two blank lines after the abstract or list three to five keywords related to the articles, then continued with abstract in bahasa Indonesia.